Lactobezoar causing neonatal gastric perforation - Smart Zeidan; Rezkalla Akkary; Nadine Jawad; Dany Al Hamod; Zaher Haidar; Nabil Diab (Elsevier, 2019)
A lacto-bezoar is an aggregation of mucus and undigested milk and can obstruct any part of the digestive tract. The diagnosis of this entity theoretically is very straight forward. However without a high index of suspicion missing it becomes inevitable. Any delay in the diagnosis can be morbid and even lethal at times.In the following report we presented two cases of neonatal gastric perforation induced by gastric lactobezoar, we highlighted the errors in diagnosis and then we summed up with a review of the literature. Keywords: Perforation, Gastric, Stomach, Premature, Lactobezoar, Pneumoperitoneum